2016
DOI: 10.1007/s12192-016-0689-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression pattern of heat shock protein 70 gene in tissues and heat stress phenotypes in goats during peak heat stress period

Abstract: It has been established that the synthesis of heat shock protein 70 (Hsp70) is temperature-dependent. The Hsp70 response is considered as a cellular thermometer in response to heat stress and other stimuli. The variation in Hsp70 gene expression has been positively correlated with thermotolerance in Drosophila melanogaster, Caenorhabditis elegans, rodents and human. Goats have a wide range of ecological adaptability due to their anatomical and physiological characteristics; however, the productivity of the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 43 publications
5
21
0
4
Order By: Relevance
“…In the present study, the expression of HSP70 in liver of pigs after 21 d of exposure to HS increased 4-fold compared to TNad. This increased HSP70 expression in liver coincides with the 5-fold increase in HSP70 expression in liver and brain of HS tolerant goats during the peak of a HS period, compared to HS susceptible goats reported by Rout et al (2016). Also Nagayach et al (2017) observed an increase in HSP70 expression in liver and heart of goats during the summer.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, the expression of HSP70 in liver of pigs after 21 d of exposure to HS increased 4-fold compared to TNad. This increased HSP70 expression in liver coincides with the 5-fold increase in HSP70 expression in liver and brain of HS tolerant goats during the peak of a HS period, compared to HS susceptible goats reported by Rout et al (2016). Also Nagayach et al (2017) observed an increase in HSP70 expression in liver and heart of goats during the summer.…”
Section: Discussionsupporting
confidence: 76%
“…La reducida expresión de HSP70 en ovejas Suffolk fue asociada con una disminución en la viabilidad de las células mononucleares sanguíneas cultivadas in vitro, y consecuentemente, con una menor adaptación a climas calientes. Es preciso señalar que la HSP70 es el marcador genético mayormente expresado en razas de ovinos y cabras adaptadas a condiciones ambientales de EC (26,27,28) . No obstante, se debe tomar en cuenta que, si bien en ovinos de pelo solamente se han logrado detectar los genes ligados con la síntesis de la HSP70, en la actualidad ya se cuenta con la identificación de varios genes asociados con la termo-tolerancia de pequeños rumiantes adaptadas al EC.…”
Section: Adaptaciones Genéticasunclassified
“…En ovinos nativos del desierto se han identificado genes de termo-tolerancia asociados con coloración y pigmentación de la piel (FGF2, GNA13, PLCB1), metabolismo energético y digestivo (MYH, TRHDE, ALDH1A3 y GPR50), y respuesta inmune (9,28,29) . Recientemente, en razas de la India adaptadas al EC también se encontraron algunas mutaciones en los polimorfismos G1270A y C888T ligados al gen GPR50, las cuales se asociaron con una mejor tolerancia térmica (29) .…”
Section: Adaptaciones Genéticasunclassified
“…These researchers suggested that individual TSSs may simply be additive, or may have expression output limitations that make transcription of additional TSSs favourable, also they suggested that having multiple TSSs could enable a faster response to stimuli 28 . Similarly, HSP genes have been extensively reported to respond to external stress stimuli 29 , so observing more variation in the number of TSSs in indicus sub-species may indicate their higher ability to respond to stress. Future research exploring a time series response could shed light on the latter hypothesis.…”
Section: Bar Charts)mentioning
confidence: 98%